Radiosynthesis and Preclinical Evaluation of 11C-VA426, a Cyclooxygenase-2 Selective Ligand. (24th September 2019) - Carpinelli, Assunta; Rainone, Paolo; Belloli, Sara; Reale, Annalisa; Cappelli, Andrea; Germano, Giuliani; Murtaj, Valentina; Coliva, Angela; Di Grigoli, Giuseppe; Valeri, Angela; Gilardi, Maria Carla; Gianolli, Luigi; et al.
Abstract : Cyclooxygenase-2(COX-2) is involved in the inflammatory response, and its recurrent overexpression in cancers as well as in neurodegenerative disorders has made it an important target for therapy. For this reason, noninvasive imaging of COX-2 expression may represent an important diagnostic tool. In this work, a COX-2 inhibitor analogue, VA426 [1-(4-fluorophenyl)-3-(2-methoxyethyl)-2-methyl-5-(4-(methylsulfonil)phenyl)-1 H -pyrrole], was synthesized and radiolabelled with the 11 C radioisotope. The ex vivo biodistribution profile of 11 C-VA426 was evaluated in the brain and periphery of healthy rats and mice and in brain and periphery of inflammation models, based on the administration of LPS. 11 C-VA426 synthesis with the t BuOK base showed optimal radiochemical yield (15 ± 2%) based on triflate activity, molar activity (range 37–148 GBq/ μ mol), and radiochemical purity (>95%). Ex vivo biodistribution studies showed a fast uptake of radioactivity but a rapid washout, except in regions expressing COX-2 (lungs, liver, and kidney) both in rats and in mice, with maximum values at 30 and 10 minutes p.i., respectively. LPS administration did not show significant effect on radioactivity accumulation. Celecoxib competition experiments performed in rats and mice treated with LPS produced a general target unrelated reduction of radioactivity concentration in all peripheral tissues and brain areas examined. Finally, in agreement with the negative results obtained from biodistribution experiments, radiometabolites analysis revealed that 11 C-VA426 is highly unstable in vivo. This study indicates that the compound 11 C-VA426 is not currently suitable to be used as radiopharmaceutical for PET imaging. This family of compounds needs further implementation in order to improve in vivo stability.